2022
DOI: 10.3991/ijim.v16i08.28689
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation for Undergraduate College Students to Learn Java Language Using E-Learning Model

Abstract: The use of modern programming in Java has become widely used in the e-learning model to help the student learn in the right place and time. Students have difficulty learning Java and are time-consuming without the benefit of understanding the material. This study presents how to build an electronic application to facilitate learning programming in modern languages. In order to confirm the effectiveness of the application, a questionnaire was developed on the need for an educational application that helps facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Within the context of smart mobile learning, interface standards emphasize the potential of mobile devices to connect learners with various resources, communities, and expertise, fostering a dynamic and participatory learning environment. As emphasized by [15], arranged learning emphasizes the significance of proper settings and social cooperation within the learning environment. The situated learning hypothesis emphasizes the significance of real-world problem-solving tasks and collaborative projects, bridging the gap between classroom teaching and practical application when it comes to mobile learning in programming.…”
Section: Systematic Literature Review For Smart Mobile Learning In Pr...mentioning
confidence: 99%
“…Within the context of smart mobile learning, interface standards emphasize the potential of mobile devices to connect learners with various resources, communities, and expertise, fostering a dynamic and participatory learning environment. As emphasized by [15], arranged learning emphasizes the significance of proper settings and social cooperation within the learning environment. The situated learning hypothesis emphasizes the significance of real-world problem-solving tasks and collaborative projects, bridging the gap between classroom teaching and practical application when it comes to mobile learning in programming.…”
Section: Systematic Literature Review For Smart Mobile Learning In Pr...mentioning
confidence: 99%
“…However, the long-term purpose for using it has been determined [7]. Additionally, results from additional studies [21] revealed that developing technologies are successfully used. Teachers and students employ technology with the goal of establishing an e-learning relationship, for example [31].…”
Section: Behaviour Intention (Bi)mentioning
confidence: 99%
“…Support assessment is the external assistance provided to pupils to help them overcome their learning challenges [27][12]. Similar to this, [21][17] used post-test objective grade distribution as a measure for student support assessment rather than the more typical post-test that centrally evaluates and grades students to evaluate student learning objectives (SLO). The impact of SA on PU was strongest in the second month of lockdown.…”
Section: Support Assessment (Sa)mentioning
confidence: 99%
“…Java is one of the most active languages in the world due to the breadth of IDEs that cover its use in their platforms, which is based on computer development [22]. Another benefit of using this programming language is that it is very simple and easy to understand [23], including high-performance development functions, sub-processes and requirements elicitation according to user needs [24], [25].…”
Section: Development Toolsmentioning
confidence: 99%